Enhancing students’ interest in Physical Education through the integration of Social Emotional Learning and Problem-Based Learning - Aji Dwi Rogo; Syamsuramel; M Armando Yusaromi (Sriwijaya Journal of Sport, 2025)
Research Problems: This research was conducted based on the low level of students’ interest in physical education learning. The current physical education learning process has not been able to fully accommodate students’ needs and interests, resulting in low engagement and enthusiasm in learning. Teaching that integrates the Social Emotional Learning (SEL) approach with the Problem-Based Learning (PBL) model is expected to facilitate diverse student characteristics and learning interests. Research Objectives: This study aimed to determine the improvement of students’ learning interest in physical education through the integrated SEL–PBL approach. Methods: The research employed a Classroom Action Research (CAR) design conducted in two cycles, each consisting of four stages: planning, implementation, observation, and reflection. Data on learning interest were collected using a learning interest questionnaire and analyzed both quantitatively and qualitatively. Results: The results showed that the average percentage of students’ learning interest before the intervention was 51.5% (low), which increased to 56.25% (moderate) after the first cycle, and further improved to 86.75% (high) after the second cycle. Conclusion: Therefore, integrating the SEL approach within the PBL model can effectively enhance students’ interest in learning physical education.